A novel method for the extraction, purification, and characterization of noble gases in produced fluids - Tyne, RL; Barry, PH; Hillegonds, DJ; Hunt, AG; Kulongoski, JT; Stephens, MJ; Byrne, DJ; Ballentine, CJ (American Geophysical Union, 2019)
Hydrocarbon systems with declining or viscous oil production are often stimulated using enhanced oil recovery (EOR) techniques, such as the injection of water, steam, and CO2, in order to increase oil and gas production. As EOR and other methods of enhancing production such as hydraulic fracturing have become more prevalent, environmental concerns about the impact of both new and historical hydrocarbon production on overlying shallow aquifers have increased. Noble gas isotopes are powerful tracers of subsurface fluid provenance and can be used to understand the impact of EOR on hydrocarbon systems and potentially overlying aquifers. In oil systems, produced fluids can consist of a mixture of oil, water and gas. Noble gases are typically measured in the gas phase; however, it is not always possible to collect gases and therefore produced fluids (which are water, oil, and gas mixtures) must be analyzed. We outline a new technique to separate and analyze noble gases in multiphase hydrocarbon-associated fluid samples. An offline double capillary method has been developed to quantitatively isolate noble gases into a transfer vessel, while effectively removing all water, oil, and less volatile hydrocarbons. The gases are then cleaned and analyzed using standard techniques. Air-saturated water reference materials (n = 24) were analyzed and results show a method reproducibility of 2.9% for 4He, 3.8% for 20Ne, 4.5% for 36Ar, 5.3% for 84Kr, and 5.7% for 132Xe. This new technique was used to measure the noble gas isotopic compositions in six produced fluid samples from the Fruitvale Oil Field, Bakersfield, California.